Implementation Measurement of Physical Test Results for Branch of Badminton Using Application - Irawati, Windi Setya; Hartati, Hartati; Yusfi, Herri (Department of Physical Education, Sport, Health and Recreation, 2024)
The study aims to assess the physical fitness of students at State Elementary School 216 Palembang through the use of an application for measuring physical test results. The research employs a quantitative descriptive method. The findings from the application-based physical test measurements reveal that 16 students fall into the